2004
DOI: 10.1111/j.1471-6402.2004.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Female Trouble: The Menstrual Self-Evaluation Scale and Women's Self-Objectification

Abstract: Strong cultural messages are sent to women that their bodies are unacceptable as they are, thus encouraging engagement in a variety of body‐altering practices. It seems that one of the obligations that women have in a culture that sexually objectifies their bodies is to conceal their bodies' more physical functions, such as menstruation. A new scale was constructed to measure women's attitudes and emotions toward menstruation. A study was conducted to test the relationship between self‐objectification and wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
103
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(106 citation statements)
references
References 13 publications
1
103
0
2
Order By: Relevance
“…Calogero, Herbozo, & Johnston-Robledo, Wares, Fricker, & Pasek, 2007;Roberts, 2004), potentially perpetuating a vicious cycle of self-objectification and body modification.…”
Section: Discussionmentioning
confidence: 99%
“…Calogero, Herbozo, & Johnston-Robledo, Wares, Fricker, & Pasek, 2007;Roberts, 2004), potentially perpetuating a vicious cycle of self-objectification and body modification.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this was the same measure of self-objectification used initially to test propositions of objectification theory. Roberts (2004) provided a recent comparison of McKinley and Hyde's (1996) Objectified Body Consciousness (OBC)-Surveillance subscale to the SOQ. This comparison demonstrated that the SOQ specifically captures the experience of viewing the body from an outsider's perspective whereas the OBCSurveillance subscale includes items related to worry and concern about how the body appears to others.…”
Section: Discussionmentioning
confidence: 99%
“…This experience of self-objectification has been theoretically and empirically linked to a variety of negative consequences in nonclinical samples of adult and adolescent women, including increased opportunities for experiencing body shame, anxiety, negative attitudes toward menstruation, a disrupted flow of consciousness, diminished awareness of internal bodily states, depression, sexual dysfunction, and disordered eating (Calogero, 2004;Fredrickson, Roberts, Noll, Quinn, & Twenge, 1998;Roberts, 2004;Slater & Tiggemann, 2002;Tiggemann & Slater, 2001). …”
mentioning
confidence: 99%
“…The following is a list (not exhaustive) of other consequences empirically associated with self-objectification: lower intrinsic motivation and self-efficacy (Gapinski, Brownell, & LaFrance, 2003); lower self-esteem (Choma et al, 2010); less life satisfaction (Mercurio & Landry, 2008); diminished cognitive performance Gay & Castano, 2010;Quinn, Kallen, Twenge, & Fredrickson, 2006); diminished physical performance (Fredrickson & Harrison, 2005); more negative attitudes toward breastfeeding (JohnstonRobeldo, Fricker, & Pasek, 2007) and reproductive functioning (Johnston-Robledo, Sheffield, Voigt, & Wilcox-Constantine, 2007;Roberts, 2004); greater fear and perceived risk of rape (Fairchild & Rudman, 2007); greater hostility toward other women (Loya, Cowan, & Walters, 2006); more self-injury (Muehlenkamp, Swanson, & Brausch, 2005); more substance abuse (Carr & Szymanski, 2011;Harell, Fredrickson, Pomerleau, & Nolen-Hoeksema, 2006); decreased use of sexual protection (Impett, Schooler, & Tolman, 2006); more dysfunctional exercise (Strelan, Mehaffey, & Tiggemann, 2003); and more support for cosmetic surgery (Calogero, Pina, Park, & Rahemtulla, 2010;Calogero, Pina, & Sutton, 2013).…”
Section: Consequences Of Self-objectificationmentioning
confidence: 99%